Epigenetically regulated miR-145 suppresses colon cancer invasion and metastasis by targeting LASP1 - Wang, Wei (Oncotarget, 2016)
MiR-145 is a tumor-suppressive microRNA that participates in the malignant progression of colorectal cancer (CRC). Although miR-145 has been reported to inhibit proliferation and to induce apoptosis of CRC cells, the reports about its role in invasion and metastasis are controversial. The regulation of miR-145 its own expression also requires further elucidation. In this study, we firstly found that miR-145 is markedly downregulated in the metastatic tumors of CRC patients. Then through gain- and loss-of function studies, we demonstrated that miR-145 suppresses the invasion and metastasis of CRC cells. We also provided experimental evidences which include direct binding assays and verifications on tissue specimens to confirm that LIM and SH3 protein 1 (LASP1) is a direct target of miR-145. Furthermore, we identified the core promoter regions of miR-145 and observed the cooperation between histone methylation and transcription factors through binding to these core promoter regions to regulate the expression of miR-145 in CRC cells. Our study provides an insight into the regulatory network in CRC cells, thus offering new targets for treating CRC patients.